Woman, Worker and Mother: the Superheroine of the 21st Century - Rodríguez Navarrete, Laura (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2019)
The insertion of women in the labor market is a clear example of historical achievement because, thanks to the struggle of many women, today, it is a reality that the female population has achieved its insertion in the labor market. However, there is still a long way to go, because, at present, there is still occupational segregation which drives to the wage gap and, even, wage discrimination. The objective pursued with this essay is to facilitate the reader a broad view of how the situation of the women in the labor market has been transforming until achieving the current situation.
Keywords: women; workers; equality; discrimination; occupational segregation; wage gap